Respuesta :

Answer:

[tex]x = \frac{360}{11} [/tex]

[tex]y = \frac{60}{11} [/tex]

Step-by-step explanation:

Since 6y=x plug 6y in for x on the top equation.

[tex]2(6y) - y = 60[/tex]

[tex]12y - y = 60[/tex]

[tex]11y = 60[/tex]

[tex]y = \frac{60}{11} [/tex]

Plug y=60/11 into 6y=x

[tex]6( \frac{60}{11} ) = x[/tex]

[tex] \frac{360}{11} = x[/tex]

Plug 360/11 into 2x-y=60

[tex]2( \frac{360}{11} ) - \frac{60}{11} = 60[/tex]

[tex] \frac{720}{11} - \frac{60}{11} = 60[/tex]

[tex] \frac{660}{11} = 60[/tex]

The identity is true